Effect of Carrot Juice Substitution and Fermentation Condition on the Characteristics of LAB-Fermented Milk Drink - Zubaidah, Elok; Saparianti, Ella; Mawardhani, Marrisa (Fakultas Teknologi Pertanian Universitas Brawijaya, 2005)
The physicochemical, microbiological and sensory characteristics of lactic acid bacteria-fermented milk drinks partly substituted with carrot juice processed at different fermentation conditions were studied. Part of the milk was substituted with carrot juice at a level of 0, 5, 10, and 15% and the fermentation condition of 37°C for 24 hours and 42°C for 8 hours employing Lactobacillus casei, respectively. It was found that the growth of the bacteria and the production of acid were higher on the product fermented at 37°C for 24 hours. A higher level of carrot juice substitution resulted in the increase of the bacteria population and acid level, but reducing the levels of sugar, ß- carotene, total soluble solids and viscosity. The best product in term of physicochemical and microbiological characteristics, was obtained by substitution of carrot juice at a level of 15% and fermentation at 37°C for 24 hours, but it had better sensory characteristics when fermented at 42°C for 8 hours. Key words: fermented milk drink, carrot juice substitution, fermentation condition